Simulating effect of anthropogenic activities and climate variation on Liulin Springs discharge depletion by using the ARIMAX model. Issue 18 (8th June 2012) - Hao, Yonghong; Wu, Jing; Sun, Qingxia; Zhu, Yuen; Liu, Yan; Li, Zhongtang; Yeh, Tian‐Chyi J.
Abstract: Based on the groundwater development process, and regional economic and social developing history, we divided the spring hydrological process of the Liulin Springs Basin into two periods: pre‐1973 and post‐1974. In the first period (i.e. 1957–1973), the spring discharge was affected by climate variation alone, and in the second period (i.e. 1974–2009), the spring discharge charge was influenced by both climate variation and human activities. A piecewise analysis strategy was used to differentiate the contribution of anthropogenic activities from climate variation on karst spring discharge depletion in the second period. Then, the ARIMAX model was applied to spring flow time series of the first period to develop a model for the effects of climate variation only. Using this model, we estimated the spring discharge in the second period solely under the influence of climate variation. Based on the water budget, we subtracted observed spring discharge from the estimated spring discharge and acquired the contribution of human activities on spring discharge depletion for the second period. The results of the analysis indicated that the contribution of climate variation to the spring discharge depletion is−0.20 m 3 /s from 1970s to 2000s. The contribution of anthropogenic activities to the spring flow depletion was −2.56 m 3 /s in 2000s, which was about 13 times more than that of climate variation. Our analysis further indicates that groundwater exploitation only accounts for 29% of the spring flow depletion due to the effects of human activities. The remaining 71% of the depletion is likely to be caused by other human activities, including dam building, dewatering during coal mining, and deforestation. Copyright © 2012 John Wiley & Sons, Ltd.